The Role of Grit in Students’ L2 Engagement in the English as a Foreign Language Classroom - Liu, Juan (Frontiers in Psychology, 2021)
Due to the rapid development of teaching and learning English as a Foreign Language (EFL), on the one hand, and the arrival of positive psychology in the process of language education, on the other hand, student engagement has been burgeoned and got a noteworthy role in the academic field. The present review attempts to investigate the relationship of grit with students’ L2 engagement, by examining both backgrounds and consequences of grit. Consequently, the effectiveness of findings for policymakers and academic experts is discussed, along with the prominence of strengthening grit in the scholastic contexts in order to cultivate character in learners and improve their prospects.